In Vitro Growth Enhancement of Ectomycorrhizal Fungus Scleroderma Bovista by Two Mycorrhizosphere Bacteria - Yadav, Anurag; Dubey, R. C.; Yadav, Kusum (Indian Forester, 2015)
Five bacterial strains namely, Bacillus subtilis MB14, Bacillus sp. MB10, Pseudomonas elongata MB11, P. fluorescens MB9 and Pseudomonas sp. MB1, isolated from banj oak (Quercus leucotrichophora A. Camus) mycorrhizosphere were tested for their effect on growth of ectomycorrhizal (ECM) fungus Scleroderma bovista in plate and flask experiment. Treatment of P. fluorescens MB9 culture filtrate on S. bovista yielded highest biomass (158.4 mg), as compared to control (94.0 mg). Moderate growth enhancement of ECM fungus was observed by B. subtilis MB14 treatment, while other three isolates moderately decreased S. bovista growth. Reduction in pH of growth medium was also observed. A strong linear regression (R2 = 0.925) between ECM fungal biomass and final pH of growth medium was observed.